2016
DOI: 10.7566/jpsj.85.034002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Phase Transition in Generalized Pólya Urn in Information Cascade Experiment

Abstract: We propose a method of detecting a phase transition in a generalized Pólya urn in an information cascade experiment. The method is based on the asymptotic behavior of the correlation C(t) between the first subject's choice and the t + 1-th subject's choice, the limit value of which, c ≡ lim t→∞ C(t), is the order parameter of the phase transition. To verify the method, we perform a voting experiment using two-choice questions. An urn X is chosen at random from two urns A and B, which contain red and blue balls… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Information cascade is the tendency to choose the majority choice even if one thinks the minority option is correct or optimal [17,18]. In laboratory experiments, at most 63 subjects answered two-choice questions one by one after observing the previous subjects' choices [19,20]. The sequential choice processes were described as non-linear Pólya urn process.…”
Section: Introductionmentioning
confidence: 99%
“…Information cascade is the tendency to choose the majority choice even if one thinks the minority option is correct or optimal [17,18]. In laboratory experiments, at most 63 subjects answered two-choice questions one by one after observing the previous subjects' choices [19,20]. The sequential choice processes were described as non-linear Pólya urn process.…”
Section: Introductionmentioning
confidence: 99%
“…In EXP-I, we studied these points and concluded that the system is self-correcting for z 0 (T ) = 70% ± 5% and 80% ± 5% [16]. Our experiment for EXP-II and its analysis are under way [17].…”
Section: Resultsmentioning
confidence: 83%
“…Our results, unlike those of previous experiments [6,7,8], show the summary statistics of the number of subjects who have chosen each urn. The length T and number of questions I are 63 and 200, respectively, for q ∈ {2/3, 5/9} [17].…”
Section: Domino Effect and Detection Of Non-self-correcting Naturementioning
confidence: 99%
“…An information cascade experiment provides a concrete setup for the physical realization of the formation of the final imbalance [9]. The change in the number of stable states can be observed by controlling the uncertainty of the subjects [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Equation (A1a) immediately yields Eq. (11). We now define u ± k (t) = e −G ± (t) y ± k (t), k = 1, 2, where G ± (t) was defined in Eq.…”
mentioning
confidence: 99%